Centering Equity and Caring in Leadership for Social-Emotional Learning: Toward a Conceptual Framework for Diverse Learners. Issue 6 (November 2019) - Kennedy, Kate
School leaders must navigate nonacademic barriers to learning. One type of affective, nonacademic reform is social-emotional learning (SEL), a quickly growing K–12 school initiative. Yet scant empirical literature exists on the actions, interactions, and beliefs of school principals charged with leading SEL reforms. The needs of diverse learners in SEL reforms—and how school leaders might create culturally relevant, gender-aware, queer-friendly SEL programming—are ignored by empirical research. This article seeks to contribute conceptually by exploring two questions: To what extent does current research inform school leadership of SEL implementation for diverse learners? How might school leaders conceptualize the implementation of SEL reforms from a caring, equity-oriented lens? A leadership framework for SEL reforms, rooted in caring and equity, is proposed.